SMA ISLAM BRAWIJAYA'S IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION MANAGEMENT - Insani, Yogie Dana; Lukmanasari, Herla; Sudarmiatin, Sudarmiatin; Firmansyah, Risky (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This paper is dedicated to describing the management of entrepreneurship education implementation., including It provides invaluable support and countering factors, at SMA Islam Brawijaya. Qualitative research with a descriptive approach is employed in this study. The process of gathering data involves observation, interviewing, and recording. The data analysis follows a structure of collection, reduction, presentation, and conclusion, grounded in empiricism. The validity of the data is ensured through source verification and triangulation techniques. The findings from research on the management of entrepreneurship education are organized into five key aspects. First, the planning for entrepreneurship education involves a straightforward approach. Second, 10th-grade teachers introduce content, 11th-grade teachers instill entrepreneurial values and attitudes, and 12th-grade teachers guide product creation. Third, the principal serves as a role model and leader. Fourth, a startup team is established for coordination within the school. Finally, monitoring occurs through student product activities, bolstered by partnerships with industry, alumni, and community support. Challenges include students' low motivation to learn entrepreneurship, limited funding, and insufficient tools for practical engagement.